2021
DOI: 10.1183/23120541.00738-2020
|View full text |Cite
|
Sign up to set email alerts
|

Targeting dynamic hyperinflation in moderate-to-severe asthma: a randomised controlled trial

Abstract: BackgroundDynamic hyperinflation (DH) is highly prevalent in moderate to severe asthma, which may significantly impede activities of daily life. We hypothesised that DH in asthma is due to inflammation of large and small airways and can be reduced by systemic anti-inflammatory treatment. Therefore, we investigated the effect of systemic glucocorticoids on DH in moderate to severe asthma patients and explored the relationships between inflammatory markers and changes in DH.MethodsIn this randomised placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The benefits of anti-inflammatory therapy on exercise capacity were previously described by VAN DER MEER et al [9], who analysed the response to corticosteroid treatment in a cohort of moderate-to-severe asthmatic patients. In their study, dynamic hyperinflation was significantly reduced by systemic glucocorticoid therapy, suggesting that anti-inflammatory treatment could improve exercise capacity and quality of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The benefits of anti-inflammatory therapy on exercise capacity were previously described by VAN DER MEER et al [9], who analysed the response to corticosteroid treatment in a cohort of moderate-to-severe asthmatic patients. In their study, dynamic hyperinflation was significantly reduced by systemic glucocorticoid therapy, suggesting that anti-inflammatory treatment could improve exercise capacity and quality of life.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, they reported that the administration of bronchodilation therapy prior to cardiopulmonary exercise testing (CPET) did not improve the exercise capacity. A randomised controlled trial was conducted by VAN DER MEER and colleagues [9] to investigate the effect of corticosteroid therapy on dynamic hyperinflation in patients with moderate-to-severe asthma. The authors found that after 2 weeks of triamcinolone therapy the degree of dynamic hyperinflation was reduced by 23.2%.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of anti-inflammatory therapy on exercise capacity were previously described by V an der M eer et al . [ 9 ], who analysed the response to corticosteroid treatment in a cohort of moderate-to-severe asthmatic patients. In their study, dynamic hyperinflation was significantly reduced by systemic glucocorticoid therapy, suggesting that anti-inflammatory treatment could improve exercise capacity and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they reported that the administration of bronchodilation therapy prior to cardiopulmonary exercise testing (CPET) did not improve the exercise capacity. A randomised controlled trial was conducted by V an der M eer and colleagues [ 9 ] to investigate the effect of corticosteroid therapy on dynamic hyperinflation in patients with moderate-to-severe asthma. The authors found that after 2 weeks of triamcinolone therapy the degree of dynamic hyperinflation was reduced by 23.2%.…”
Section: Introductionmentioning
confidence: 99%